Voluntary Enrolment - A Viable Way of Staffing Projects? - Pernille Eskerod; Anna Lund Jepsen (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2004)
Traditionally allocation of personnel for projects has been seen as a manage-ment task. Recently, however, more and more organisations are treading new paths when staffing projects. In this article we examine a new staffing proce-dure, in which enrolment is dependent on employees voluntarily responding to internal advertising of projects. An important issue in voluntary enrolment is the employees decision to enrol or not. To investigate the enrolment decision process, we develop a model that we call the Enrolment Readiness Model. The key concept in the model is enrolment readiness, which is a concept we develop to depict intention to enrol as the outcome of a decision process trig-gered by the awareness of a project being advertised. The model is tested in a municipal administration organisation that has staffed projects by voluntary en-rolment for a number of years. The case study mainly confirms the proposed model, but also clarifies that voluntary enrolment may cause problems in get-ting a sufficient number of participants in the proposed projects. The article concludes by stressing that voluntary enrolment seems to require more attention and effort from top management than a traditional/conventional staffing proce-dure and we propose ways that the Enrolment Readiness Model can be helpful in supporting voluntary enrolment. An early version of this paper was presented at the research conference, pm days 03, Vienna, Austria, October 2003.
Keywords: 330; Staffing; Enrolment; Enrolment Readiness Model; Renewal Pro-jects; Human Resource Management; Projektmanagement; Personalauswahl; Personalmanagement